Prevalence of factor V gene G1691A (Leiden)- factor V gene H1299R mutations and prothrombin gene G20210A mutations in Turkish population: Factor V G1691A-H1299R and Prothrombin G20210A Mutations - Ünallı Özmen, Sevda (Journal of Medical Biochemistry, 2025)
Thrombosis is one of the critical health problems worldwide that is a reason for mortality and morbidity. Factor V and Prothrombin gene mutations are the most common genetic risk factors related to thrombotic events. We aimed to explore these mutations in a healthy population and compare them with coronary artery disease (CAD) patients. A total of 406 healthy volunteer individuals and 64 patients with CAD were included in the study. Factor V gene G1691A-H1299R and prothrombin gene G20210A mutations were determined using the CVD StripAssay, based on the reverse-hybridization principle for mutation analysis. Factor V Leiden G1691A gene mutation was identified in 8 (12,49%), prothrombin G20210A gene mutation was identified in 1 (1.56 %), and Factor V H1299R gene mutation was identified in 9 (14,07 %) in the CAD patient group. No significant difference between the CAD and control groups was evident in all three genes. The prevalence of Factor V G1691A-H1299R / prothrombin gene G20210A G20210A mutation in CAD was found to be very low and similar to the general population. Keywords: Factor V G1691A-H1299R Mutations, Prothrombin G20210A Mutations, coronary artery disease